P-406 Ongoing pregnancy rates (OPRs) after warmed blastocyst transfer (WBT) in a true-natural cycle (t-NC) are similar using six different luteinizing hormone (LH) surge criteria. (30th June 2022) - Erden, M; Polat, M; Mumusoglu, S; Ozbek, I. Y; Gonca, O.D; Karakoc Sokmensuer, L; Esteves, S; Humaidan, P; Yarali, H
Abstract: Study question: Does timing of WBT in t-NC differ according to six different commonly definitions for LH surge, and if so, do differences in timing impact OPRs? Summary answer: Performing WBT on follicular collapse+5 days is equivalent to LH surge +7/+8 /+9 days in terms of OPRs, using six different definitions of LH surge. What is known already: Pinpointing the day of ovulation, usually by documentation of the LH surge, and less commonly by transvaginal-ultrasonography is crucial for timing WBT in t-NC to maximize reproductive success. However, there is no consensus on the definition of the LH surge, and the most commonly used six LH-surge definitions are LH ≥ 10, ≥15, ≥17, ≥20 IU/L, ≥1.8-fold, and ≥2-fold increase from baseline. The usual practice is to schedule warmed blastocyst transfer on LH-surge +6 days. Study design, size, duration: Prospective monitoring of 115 WBT cycles performed during January 2017-October 2021. The goals of the study were i)to assess how frequently and to what extent there would be a change in WBT related to the day of the LH surge, using the six different definitions of LH surge, compared to follicular collapse +5 days; ii)for each definition of the LH surge to compare OPRs of different WBT timings related to the day of LH surge. Participants/materials, setting, methods: Staying locally and having regular menstrual cycles were the main criteria to perform t-NC. For t-NC, serial serum endocrine (LH, estradiol, and progesterone) and transvaginal ultrasonographic monitoring started on cycle days 8-10. Following precise documentation of follicular collapse by ultrasound, WBT was performed on follicular collapse +5 days. All included cycles were t-NC without human chorionic gonadotropin trigger or luteal phase support administration. Main results and the role of chance: A total of 115 t-NC cycles were included for the first part of the study, determining the impact of different definitions of the LH-surge for the day of WBT. Our reference timing of follicular collapse +5 days would be equivalent to LH-surge +6 days in only 5.2%-41.2% of the cycles employing the six different LH-surge definitions. In contrast, the reference timing was comparable to LH surge +7 days in the majority of cycles (46.1%-70.8%) and less commonly to LH-surge +8 days (1.8%-38.3%) and +9 days (0%-10.4%). For the second part of the study, a total of 94 cycles were analyzed; 15 cycles were excluded as these cycles constituted 2 nd or 3 rd t-NC cycles; four cycles due to low serum progesterone (<7 ng/ml) on WBT-1 day and two cycles due to failure of survival after warming. For each LH-surge definition, OPRs were comparable among the different WBT timings related to the LH-surge (+6/+7/+8/+9 days). When logistic regression analysis was performed, taking LH-surge + 6 days as the reference, a change in timing was not an independent predictor of OPR for all six different definitions of the LH-surge. Limitations, reasons for caution: Assignment of WBT timings related to LH-surge by our standard policy (follicular collapse +5 days), rather than by randomization, is a limitation. Other limitations include single daily measurements of serum LH and limited sample size. Wider implications of the findings: Differences in warmed blastocyst timing related to the LH surge (LH surge +6/+7/+8/+9) are associated with comparable reproductive outcomes in t-NC, reflecting the flexibility of the window of implantation. Further, trials are warranted to delineate the best tool and timing of FET for warmed blastocyst transfer in t-NC. Trial registration number: Not applicable